DIABETIC FOOT: A SCOPING REVIEW OF NEUROSENSORIC DISORDERS – THERMOGRAPHY - Lenny Nurhandayani; Sri Andarini; Heri Kristianto (Syntax Corporation Indonesia, 2023)
Background: Diabetic foot is a chronic complication that can be detrimental and has an impact on the quality of life of diabetic patients. Neurosensory examination of skin temperature using a thermograph can help prevent diabetic foot. Objective: to identify the neurosensory examination of skin temperature using infrared thermographs in addressing the risk of diabetic foot Design: The design in this study is Scoping review Methods: A journal search was conducted using the keywords